Ecological modernisation and renewable energy - Toke, David (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"Develops a new theory of 'identity' ecological modernization (EM), to analyse renewable history and policy development in many of the world's states which are leading the drive to install renewable energy. 'Identity EM' concerns how an industry has arisen allied to environmental NGOs to challenge the ascendancy of conventional energy technologies"--
Machine generated contents note: -- Introduction -- Revising Ecological Modernisation Theory -- Renewable Energy: a new identity and a new industry -- California- The Growth of a Renewables Industry -- USA: Consolidation of a Renewables Industry? -- Germany, Spain, UK, Australia and China -- Conclusion.
Includes bibliographical references and index.
Book Aid International 2021 Donated by Bhutan Society of the UK Trust Fund.
Keywords: Renewable energy sources; Energy development; Energy policy; POLITICAL SCIENCE / Public Policy / Environmental Policy; POLITICAL SCIENCE / Globalization; POLITICAL SCIENCE / Government / National